Jean Dubuffet : a study of his concepts pertaining to the alienation of the artist - Mather-Pike, Richard (Rhodes University, Faculty of Humanities, Department of Fine Art, 1989)
I decided on an investigation into the nature of Dubuffet's remarks concerning the plight of the artist in modern societies, believing that the difficulties facing the artist are, at the time of this writing, still in force, and perhaps even more so now than they were in his day. These difficulties I believe, arise in the form of curtailments on personal and aesthetic freedoms brought about as the result of the artist's position in, and conformity to, the norms and values of his society. The problem is I believe, that these value systems not only censor or curb artistic freedom but actually restrict all individual enterprises by demanding that the indi vidual conform to the greater wish of the group, at the expense of his own creative and individual potential.
Keywords: Uncatalogued